PENERAPAN KETENTUAN PASAL 42 UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN DALAM PENYIDIKAN TINDAK PIDANA PENIPUAN MELALUI MEDIA ELEKTRONIK DI SUBDIT V DIREKTORAT RESERSE KRIMINAL KHUSUS KEPOLISIAN DAERAH RIAU - Putra, Yanda Syahrul Qotni; Erdiansyah, Erdiansyah; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The crime of fraud through electronic media is one of the cyber crimes that existtoday, and the regulation related to this crime has also been regulated in Article 28Paragraph (1) of the Law on Electronic Information and Transactions. However, theenforcement of the regulation can be considered less than optimal because during thehandling, especially during the investigation, there are several obstacles that occur, and oneof these obstacles is due to the existence of Article 42 of Law Number 10 of 1998 concerningBanking which causes obstacles to an effective investigation process. The main problems inthis research are: How is the application of Article 42 of Law Number 10 of 1998concerning Banking in the investigation of criminal acts of fraud through electronic mediain Subdit V of the Special Criminal Investigation Directorate of Riau Police; What are theobstacles faced by investigators of Subdit V of the Special Criminal InvestigationDirectorate of Riau Police in applying the provisions of Article 42 of Law Number 10 of1998 concerning Banking in investigating criminal acts of fraud through electronic media;What efforts are made by investigators of Subdit V of the Special Criminal InvestigationDirectorate of Riau Police in applying the provisions of Article 42 of Law Number 10 of1998 concerning Banking in investigating criminal acts of fraud through electronic media.The type of research conducted is sociological legal research conducted at SubDirectorate V of the Special Criminal Investigation Directorate of Riau Police. The datasources used are primary data and secondary data. The data collection techniques used areinterviews and literature review. The data is then analyzed which is descriptive, evaluativeand prescriptive to be concluded using a deductive method of thinking.The results of this research are the application of Article 42 of Law Number 10 of1998 concerning Banking in the investigation of criminal acts of fraud through electronicmedia in Subdit V of the Special Criminal Investigation Directorate of Riau Police in theinvestigation of criminal acts of fraud through electronic media, where the regulation arisesif the investigator wants to disclose information related to bank secrets, especiallyinformation about customers.Keywords: Application - Crime - Fraud - Electronic Media